(untitled) (Al-Academy, 2021)
This research reviews the aesthetic variables that were founded according to (theatrical rehearsal) as one of the most important pillars on which the theatrical process is based, because of its necessity in developing theatrical art on several levels that helped the theatrical director in organizing his work, and this became clear through the research chapters represented in the first chapter (methodological framework) and the second chapter, which consisted of the first topic (the duality of watching / rehearsal) and the second topic (the applications of theatrical rehearsal in theatrical experiences), all the way to the third chapter (research procedures), which included the analysis of theatrical rehearsals (sharing on life), and the fourth chapter ( results and conclusions), and we mention some of them:1- Time has an active presence in the theatrical rehearsal, as the director worked on dividing the rehearsals into stages, each associated with a specific time period.2- The directors’ work in the rehearsal revealed different levels of the goals that the director seeks to achieve, so some of them went to the interpretation of the theatrical rehearsal as the place where his ideas and plans are implemented, and others considered it a laboratory for research and discovery